New Estimates of the q-Hermite–Hadamard Inequalities via Strong Convexity - Sahatsathatsana, Chanokgan; Yotkaew, Pongsakorn (Axioms, 2025)
A refined version of the q-Hermite–Hadamard inequalities for strongly convex functions is introduced in this paper, utilizing both left and right q-integrals. Tighter bounds and more accurate estimates are derived by incorporating strong convexity. New q-trapezoidal and q-midpoint estimates are also presented to enhance the precision of the results. The improvements in the results compared to previous work are demonstrated through numerical examples in terms of precision and tighter bounds, and the advantages of using strongly convex functions are showcased.